Establishing common ground with the audience: an analysis of American commencement addresses - Bogdanowska-Jakubowska, Ewa (Penerbit Universiti Kebangsaan Malaysia, 2023)
Successful communication requires establishing common ground with other participants through shared knowledge and experiences, whether in private conversations, workplace meetings, or speeches given to large audiences. The aim of the study is to analyze strategies of establishing common ground employed in American commencement addresses. The data used in the analysis comes from the corpus of 100 commencement addresses delivered in American universities and colleges. Commencement address, which constitutes an important element of commencement ceremony, is deeply rooted in the American university tradition. It is a recognizable communicative event characterized by a set of communicative purposes, such as celebrating academic achievements, honoring graduates, and giving them advice for the future. The audience comprises graduates, their families, friends, and faculty, while the speakers are notable figures in American society. The analysis adopts the Discourse-Historical Approach, committed to Critical Discourse Studies. The data has been analyzed in terms of strategies of establishing common ground, argumentation schemes and linguistic means used to realize the strategies. In the analyzed discourse, five strategies of establishing common ground have been identified: reference to similar/common experiences; self-disclosure; reference to common beliefs, values and practices; reference to common identity; and the use of humor. The findings emphasize the importance of claiming common ground with the audience for public addresses (including commencement speeches) to be successful. Despite the diversity of cultural backgrounds, social status and professions, and generational differences among the speakers, the interaction between them and the audience, the graduates in particular, generally proceeds smoothly, although the speakers' attempts to establish common ground with the audience are not always successful.